Interventional oncologic approaches to liver metastases - Mahnken, Andreas H.; Pereira, Philippe L.; Baère, Thierry de (Radiology, 2013)
Metastatic liver disease is the most common cause of death in cancer patients. Complete surgical resection is currently considered the only curative treatment, with only about 25% of patients being amenable to surgery. Therefore, a variety of interventional oncologic techniques have been developed for treating secondary liver malignancies. The aim of these therapies is either to allow patients with unresectable tumors to become surgical candidates, provide curative treatment options in nonsurgical candidates, or improve survival in a palliative or even curative approach. Among these interventional therapies are transcatheter therapies such as portal vein embolization, hepatic artery infusion chemotherapy, transarterial chemoembolization, and radioembolization, as well as interstitial techniques, particularly radiofrequency ablation as the most commonly applied technique. The rationale, application and clinical results of each of these techniques are reviewed on the basis of the current literature. Future prospects such as gene therapy and immunotherapy are introduced.© RSNA, 2013
Gesehen am 15.06.2021